EVIDENCE OF ATMOSPHERIC RESPONSE TO METHANE EMISSIONS FROM THE EAST SIBERIAN ARCTIC SHELF - Natalia Pankratova; Andrey Skorokhod; Igor Belikov; Nikolai Elansky; Vadim Rakitin; Yury Shtabkin; Elena Berezina (Geography, Environment, Sustainability, 2018)
Average atmospheric methane concentration (CH4) in the Arctic is generally higher than in other regions of the globe. Due to the lack of observations in the Arctic there is a deficiency of robust information about sources of the methane emissions. Measured concentrations of methane and its isotopic composition in ambient air can be used to discriminate sources of CH4. Here we present the results of measurements of the atmospheric methane concentration and its isotope composition (δ13CCH4) in the East Siberian Arctic Seas during the cruise in the autumn 2016. Local sections where the concentration of methane in the near-water layer of the atmosphere reaches 3.6 ppm are identified. The measurements indicated possibility of formation of high methane peaks in atmospheric surface air above the East Siberian Arctic Shelf (ESAS) where methane release from the bottom sediments has been assumed.